Diseño de un plan estratégico para incentivar el turismo en la comuna Puerto Engabao, cantón Playas prov. del Guayas - Miranda Mejía, Doris Verónica (2014)
The tourism activity is associated by some standards, these are: Social, cultural, environmental and economic world, for various reasons such as: recreation, entertainment, vacations, etc. So in Latin America continues to promote tourism that contributes to the wealth of countries, developing bonds of friendship, brotherhood and understanding among peoples. The situation of tourism in Ecuador has improved in recent years, on the grounds that the current government is giving more importance to the sector to develop and maximize this activity……